Desalination Technologies for Developing Countries: A Review - Islam, M. S.; Sultana, A.; Saadat, A. H. M.; Islam, M. S.; Shammi, M.; Uddin, M. K. (Journal of Scientific Research, 2018)
Fresh water is rapidly being exhausted due to natural and anthropogenic activities. The more and more interest is being paid to desalination of seawater and brackish water in order to provide fresh water. The suitability of these desalination technologies is based on several criteria including the level of feed water quality, source of energy, removal efficiency, energy requirement etc. In this paper, we presented a review of different desalination methods, a comparative study between different desalination methods, with emphasis on technologies and economics. The real problem in these technologies is the optimum economic design and evaluation of the combined plants in order to be economically viable for the developing countries. Distillation plants normally have higher energy requirements and unit capital cost than membrane plants and produces huge waste heat. Corrosion, scaling and fouling problems are more serious in thermal processes compare to the membrane processes. On the other hand, membrane processes required pretreatment of the feed water in order to remove particulates so that the membranes last longer. With the continuing advancement to reduce the total energy consumption and lower the cost of water production, membrane processes are becoming the technology of choice for desalination in developing countries.